2022
DOI: 10.3390/biom12020323
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Stimulates Proliferation Capacity, Expression of Pluripotency Markers, and Osteogenesis of Human Bone Marrow Mesenchymal Stromal/Stem Cells, Partly through SIRT1 Signaling

Abstract: The biology of vitamin D3 is well defined, as are the effects of its active metabolites on various cells, including mesenchymal stromal/stem cells (MSCs). However, the biological potential of its precursor, cholecalciferol (VD3), has not been sufficiently investigated, although its significance in regenerative medicine—mainly in combination with various biomaterial matrices—has been recognized. Given that VD3 preconditioning might also contribute to the improvement of cellular regenerative potential, the aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 83 publications
0
9
0
4
Order By: Relevance
“…В експериментальних умовах у культурах МСК людини та остеобластах проведено порівняльний аналіз дії вітаміну D (холекальциферол, 25(OH)D 3 ) і його активного метаболіту (1α,25(OH) 2 D 3 ). Встановлено, що під їхньою дією експресія гена RUNX2, плюрипотентних маркерів NANOG, SOX2 і Oct4 посилюється в МСК людини, що свідчить про диференціювання цих клітин в остеогенному напрямку та відзначається накопиченням кальцію в позаклітинному матриксі [25,26]. Доведено зміну морфології МСК людини у бік остеобластичного феноти пу та підвищення продукції маркерів остеобластів -лужної фосфатази, остеопонтину та остеокальцину.…”
Section: вплив вітаміну D на остеобластиunclassified
See 2 more Smart Citations
“…В експериментальних умовах у культурах МСК людини та остеобластах проведено порівняльний аналіз дії вітаміну D (холекальциферол, 25(OH)D 3 ) і його активного метаболіту (1α,25(OH) 2 D 3 ). Встановлено, що під їхньою дією експресія гена RUNX2, плюрипотентних маркерів NANOG, SOX2 і Oct4 посилюється в МСК людини, що свідчить про диференціювання цих клітин в остеогенному напрямку та відзначається накопиченням кальцію в позаклітинному матриксі [25,26]. Доведено зміну морфології МСК людини у бік остеобластичного феноти пу та підвищення продукції маркерів остеобластів -лужної фосфатази, остеопонтину та остеокальцину.…”
Section: вплив вітаміну D на остеобластиunclassified
“…Доведено зміну морфології МСК людини у бік остеобластичного феноти пу та підвищення продукції маркерів остеобластів -лужної фосфатази, остеопонтину та остеокальцину. Також висловлено припущення, що контроль енергетичного метаболізму може бути мішенню вітаміну D у формуванні кісткової тканини та її мінералізації [26].…”
Section: вплив вітаміну D на остеобластиunclassified
See 1 more Smart Citation
“…However, it seems reasonable to suggest that some forms of hip fracture in older populations that are often not treated for possible osteoporotic risk 24 may derive some independent or collective benefit from vitamin D supplementation as far as reducing hip fracture incidence rates as well as mortality rates or further fractures post hip fracture surgery in vulnerable older adults. [24][25][26][27][28] In combination with silicon a recent basic study has revealed some degree of vitamin D influence on bone structure restoration and improved calcium absorption that appears to offer a possible avenue for enhancing bone related regeneration and that may prove valuable to examine further in the realm of hip fracture prevention and that is supported by human clinical evidence, [29][30][31][32] even though its presence may not impact number of falls or injurious falls that often lead to hip fractures. 33 However, there are multiple contrary study findings as well as multiple design problems that remain in this body of research, even though more favorable potentially relevant clinical findings prevail than not.…”
Section: Specific Observationsmentioning
confidence: 99%
“…Studies have examined the relationship between vitamin D with SIRT1 and Nrf2. Vitamin D increases the osteogenic potential of BMSCs by raising SIRT1 (Borojević et al, 2022). Vitamin D is also found to regulate Nrf2 to inhibit oxidative stress and DNA damage in order to play a role in delaying senescence .…”
Section: Introductionmentioning
confidence: 99%